2009
DOI: 10.1002/lary.20078
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics in head and neck surgery in the setting of malnutrition, tracheotomy, and diabetes

Abstract: Malnutrition and tracheotomy were associated with a higher infection rate while diabetes was not found to be a risk factor. Prolonged antibiotics were not associated with a lower infection rate in the overall group or in any subgroup.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 14 publications
4
42
0
4
Order By: Relevance
“…Studies of cleancontaminated head and neck procedures found no difference in efficacy between regimens of 24 hours and longer regimens of three, five, or seven days. [499][500][501]505,507,512,524,[531][532][533][534] Limited data exist on single-dose prophylaxis in these procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 98%
See 2 more Smart Citations
“…Studies of cleancontaminated head and neck procedures found no difference in efficacy between regimens of 24 hours and longer regimens of three, five, or seven days. [499][500][501]505,507,512,524,[531][532][533][534] Limited data exist on single-dose prophylaxis in these procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 98%
“…Similar results were reported in several additional small, uncontrolled studies. 500,[527][528][529] Choice of agent. Several randomized, single-center studies have compared antimicrobial regimens for clean-contaminated procedures.…”
Section: Head and Neck Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Individual patient-specific factors that might influence the risk of postoperative wound infection, are for example age, nutritional status, comorbidities such as diabetes mellitus, anemia, and peripheral vascular diseases, but also tobacco abuse, alcohol abuse, and medication [238], [239], [240], [241], [242], [243], [244], [245]. The presence of malignant disease is also a risk factor for the occurrence of wound infection.…”
Section: Evidence Of Perioperative Antibiotic Therapy In the Contexmentioning
confidence: 99%
“…CAİ için risk faktörleri yaş, beslenme durumu, diabetes mellitus, anemi, periferik vasküler hastalık, preoperatif radyasyon ve/veya kemoterapi, sigara ve alkol kullanımıdır (40)(41)(42). Radikal ya da bilateral boyun diseksiyonu ve myokutanöz flep ya da mikrovasküler serbest fleplerle rekonstrüksiyon operasyonları CAİ açısından riskli prosedürlerdir (40,42).…”
Section: Baş-boyun Cerrahisiunclassified